How Australian Health Care Services Adapted to Telehealth During the COVID-19 Pandemic: A Survey of Telehealth Professionals - Alan Taylor; Liam J. Caffery; Hailay Abrha Gesesew; Hailay Abrha Gesesew; Alice King; Abdel-rahman Bassal; Kim Ford; Jane Kealey; Anthony Maeder; Michelle McGuirk; Donna Parkes; Paul R. Ward (Frontiers Media S.A., 2021)
Background: In Australia, telehealth services were used as an alternative method of health care delivery during the COVID-19 pandemic. Through a realist analysis of a survey of health professionals, we have sought to identify the underlying mechanisms that have assisted Australian health services adapt to the physical separation between clinicians and patients.Methods: Using a critical realist ontology and epistemology, we undertook an online survey of health professionals subscribing to the Australian Telehealth Society newsletter. The survey had close- and open-ended questions, constructed to identify contextual changes in the operating environment for telehealth services, and assess the mechanisms which had contributed to these changes. We applied descriptive and McNemar's Chi-square analysis for the close-ended component of the survey, and a reflexive thematic analysis approach for the open-ended questions which were framed within the activity based funding system which had previously limited telehealth services to regional Australia.Results: Of the 91 respondents most (73%) reported a higher volume of telephone-based care since COVID and an increase in use of video consultations (60% of respondents). Respondents felt that the move to provide care using telehealth services had been a "forced adoption" where clinicians began to use telehealth services (often for the first time) to maintain health care. Respondents noted significant changes in managerial and medical culture which supported the legitimisation of telehealth services as a mode of access to care. The support of leaders and the use personal and organisational networks to facilitate the operation of telehealth service were felt to be particularly valuable. Access to, and reliability of, the technology were considered extremely important for services. Respondents also welcomed the increased availability of more human and financial resources.Conclusions: During the pandemic, mechanisms that legitimise practise, build confidence, support relationships and supply resources have fostered the use of telehealth. This ongoing interaction between telehealth services, contexts and mechanisms is complex. The adoption of telehealth access to enable physically separated care, may mark a "new context;" or it could be that once the pandemic passes, previous policies and practises will re-assert themselves and curb support for telehealth-enabled care.